Transesophageal echocardiography related complications - Zhang, Linyue; Xie, Yuji; Ren, Zhaoli; Xie, Mingxing (Frontiers in Cardiovascular Medicine, 2024)
Transesophageal Echocardiography (TEE) is an important imaging method for the evaluation of cardiac structure and function, and it holds significant value in the clinical management of cardiovascular diseases. Unlike transthoracic echocardiography (TTE), which is non-invasive, TEE involves semi-invasive intracavity operations, leading to increasing attention to its safety and potential complications. Especially with the increasing demand for TEE applications in clinical practice and the rapid growth in the number of facilities utilizing it, the standardized application and safe operation of TEE technology have become particularly crucial. This article will review the literature and draw upon personal experience to analyze the complications and safety of TEE examinations from a technical perspective.